2009
DOI: 10.1152/ajprenal.00186.2009
|View full text |Cite
|
Sign up to set email alerts
|

S6 kinase 1 knockout inhibits uninephrectomy- or diabetes-induced renal hypertrophy

Abstract: Removal of one kidney stimulates synthesis of RNA and protein, with minimal DNA replication, in all nephron segments of the remaining kidney, resulting in cell growth (increase in cell size) with minimal cell proliferation (increase in cell number). In addition to the compensatory renal hypertrophy caused by nephron loss, pathophysiological renal hypertrophy can occur as a consequence of early uncontrolled diabetes. However, the molecular mechanism underlying renal hypertrophy in these conditions remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 58 publications
(92 reference statements)
9
76
0
Order By: Relevance
“…Consistent with the studies of Chen et al, 18,19 we found that unilateral nephrectomy increased mTOR activity. Additionally, we found that mTOR activity also increased upon deletion of cilia.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with the studies of Chen et al, 18,19 we found that unilateral nephrectomy increased mTOR activity. Additionally, we found that mTOR activity also increased upon deletion of cilia.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies by Chen et al 18,19 have provided persuasive evidence that elevated mTOR activity is involved in renal hypertrophic responses to unilateral nephrectomy or to the induction of diabetes. Importantly, knockout of S6 kinase, a key enzyme downstream from mTOR, effectively eliminates most hypertrophy in response to nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Their results demonstrated that uninephrectomy induced mTORC1 signaling and renal hypertrophy without cyst formation in wild-type (WT) mice; however, uninephrectomy activated excessive mTORC1 signaling, triggered increased renal hypertrophy and accelerated renal cyst formation, leading to renal dysfunction in conditional ift88 knockout mice. 16 Of interest, mTORC1 activation also mediates both diabetes-induced renal growth [17][18][19] and phosphatase and tensin homolog deletion-induced renal growth. 15 Homozygous knockout of S6K1 blunts both uninephrectomyand diabetes-induced renal growth, 17 and phosphorylated rpS6 is a major effector downstream of mTORC1 activation in mediating compensatory renal growth.…”
mentioning
confidence: 99%